Using Green Emitting Phosphor for Improving Lighting Performance of In-cup Package White LED Lamps - Phu Tran Tin; Nguyen Huu Khanh Nhan; Tran Hoang Quang Minh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
LED technology had a huge development in recent years with major benefits: long-life, high-efficiency, excellent performance, compactness. In this work, an innovative method for improving the performance of multi-chip white LED lamps (MCW-LEDs) by adding the green Ce0.67 Tb0.33 MgAl11 O19:Ce,Tb (CeTb) phosphor to their in-cup phosphor compounding is proposed, investigated and demonstrated. Firstly, CeTb was mixed to the in-cup phosphor package of MCW-LEDs. Then by varying CeTb concentration, lumen output and angular color uniformity (ACU) of MCW-LEDs was calculated and analyzed. The results showed that the lumen output and the ACU of 7000 K and 8500 K MCW-LEDs increased significantly in comparison with others related works. This method is a prospective ideal for future improving LED manufacture.